2021
DOI: 10.1002/jcop.22544
|View full text |Cite
|
Sign up to set email alerts
|

Living in opposition: How women in the United States cope in spite of mistrust of federal leadership during the pandemic of Covid‐19

Abstract: International research collaborators conducted research investigating sociocultural responses to the Covid-19 pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
6
0
1
Order By: Relevance
“…A few recent studies have already reported the main contribution of SOC to coping with the COVID-19 pandemic. SOC was correlated with emotional distress among different cultural groups ( Barni et al., 2020 , Braun-Lewensohn et al., 2021 ) SOC was reported as a better predictor of mental health than demographic variables (e.g., gender, age, and education); risk factors (e.g., health and economic level of risk); or other coping resources (e.g., trust, family support) in different social contexts during the acute stage of the pandemic ( Généreux & Roy, 2020 ; Hardy et al., 2021 ; Mana & Sagy, 2020 ; Mana et al., in press ).…”
Section: Introductionmentioning
confidence: 99%
“…A few recent studies have already reported the main contribution of SOC to coping with the COVID-19 pandemic. SOC was correlated with emotional distress among different cultural groups ( Barni et al., 2020 , Braun-Lewensohn et al., 2021 ) SOC was reported as a better predictor of mental health than demographic variables (e.g., gender, age, and education); risk factors (e.g., health and economic level of risk); or other coping resources (e.g., trust, family support) in different social contexts during the acute stage of the pandemic ( Généreux & Roy, 2020 ; Hardy et al., 2021 ; Mana & Sagy, 2020 ; Mana et al., in press ).…”
Section: Introductionmentioning
confidence: 99%
“…Viral dissemination may even be facilitated, if normal social interactions are restored and social distancing measures are eliminated, as countries face ever increasing social and economic pressures [ 10 - 12 ]. Moreover, many people experience a rather intense state of tiredness [ 13 - 15 ] coupled with a rather high degree of mistrust toward public health authorities [ 2 , 16 - 18 ], which can result in a rapidly progressive slackening of infection prevention and control procedures [ 19 - 21 ] and which may even affect health care workers [ 22 ]. Switzerland is no exception, and conspiracy theories also thrive in this country [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…This belief exists due to acculturation, social resilience and the culture of a homogeneous community and still holds traditional values from generation to generation (Casmana, Dewantara, Timoera, Kusmawati, & Syafrudin, 2022 ; Halimah, Arifin, Yuliariatiningsih, Abdillah, & Sutini, 2020 ). Psychologically, this is even significant between the geographical and cultural aspects of the way people think, behave and believe during the COVID‐19 pandemic (Hardy et al, 2021 ). In indigenous peoples, beliefs rooted in cultural traditions have a stronger influence on people's psychology than government policies (Efriani, Donatianus, & Dewantara, 2020 ).…”
Section: Discussionmentioning
confidence: 99%